Proximal Femoral Morphometry of Adult Nepalese Presenting to a Tertiary Healthcare Centre - Gautam, Saroj; Pokharel, Rohit Kumar; Khanal, U (Nepal Orthopaedic Association Journal, 2016)
INTRODUCTION: A variation in morphometric parameters of the proximal femur has been observed among different population. The management of many of the hip pathologies involve the restoration of normal or near normal anatomy of the hip via corrective surgeries and application of prosthetic devices.Our current knowledge regarding the morphology of human skeleton however is primarily based on the studies performed in the population of the developed countries which is different from ours with respect to geography, race, nutrition, lifestyle etc.A study of proximal femoral morphometry in our own population wouldtherefore provide valuable information with wide range of utility. METHODS: A prospective observational study was carried out in 142 patients aged 18 years and above presenting to ER and Orthopedic OPD ofTribhuvan University Teaching Hospital (TUTH) in 2013. The participants underwent AP radiographs of pelvis with bilateral hips in standard technique. The measurements were then taken in digital copy of X-ray from one of the hips. RESULTS: The average values of proximal femoral morphometric parameters were found to be as follows: Hip Axis Length (HAL): 115.8± 8.92mm, Neck Axis Length (NAL): 103 ± 7.55mm, Head Width (HW): 49.5 ± 3.56mm, Neck Width (NW) : 32.3± 3.15mm, Trochanteric Width (TW): 58.9 ± 4.48mm and Neck Shaft Angle (NSA) : 125 ± 3.27°. Significant differences were found in HAL, NAL, HW, NW and TW between male and female participants; however, there was no significant difference in NSA between the two categories. Nearly 88.5% of the people had NSA between 120 to 130 degrees. CONCLUSION: The proximal femoral morphometric parameters of adultNepaleseis unique. NSA in particular is lower than 130 degrees in majority.